2021
DOI: 10.21203/rs.3.rs-609136/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison Between Percutaneous Kyphoplasty And Percutaneous Vertebroplasty In Terms of The Efficacy For Osteoporotic Vertebral Compression Fractures: A Meta-Analysis

Abstract: Background & Aim: Osteoporotic vertebral compression fractures (OVCFs) are acknowledged as common occurred fractures among humans, especially for the elderly population. The minimally invasive percutaneous methods such as kyphoplasty as well as vertebroplasty have been valid and effective tools in terms of reducing clinical problems, which are associated with more beneficial effects as compared to traditional methods such as open surgery or conservative treatment. Hence, we conducted the current meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…9 studies [21,30,35,36,53,[55][56][57][58] reported the T-score of 1543 patients after treatment in 2 groups, including 772 patients in the observation group and 771 patients in the control group. After subgroup meta-analysis, the heterogeneity test (I² = 96.2%, P < .00001) indicated significant heterogeneity among the studies, and subgroup analysis was required.…”
Section: T-score Analysismentioning
confidence: 99%
“…9 studies [21,30,35,36,53,[55][56][57][58] reported the T-score of 1543 patients after treatment in 2 groups, including 772 patients in the observation group and 771 patients in the control group. After subgroup meta-analysis, the heterogeneity test (I² = 96.2%, P < .00001) indicated significant heterogeneity among the studies, and subgroup analysis was required.…”
Section: T-score Analysismentioning
confidence: 99%
“…Further high-quality multicenter randomized controlled trials with longer follow-up and larger sample sizes are needed, but at this time indicate that there are no significant differences between PVP and BKP in terms of VAS score, ODI score, or cement leakage, and that both are useful treatments for patients with OVF [ 25 - 34 ].…”
Section: Are Orthotics Useful For Ovf?mentioning
confidence: 99%
“…Further high-quality multicenter randomized controlled tri-als with longer follow-up and larger sample sizes are needed, but at this time indicate that there are no significant differences between PVP and BKP in terms of VAS score, ODI score, or cement leakage, and that both are useful treatments for patients with OVF. [25][26][27][28][29][30][31][32][33][34] On the other hand, a systematic review comparing BKP and PVP, focusing on the primary outcome of height restoration and the secondary outcomes of pain relief and function (33 total randomized controlled trials; 20 BKP, 7 PVP, and 6 comparing PVP to BKP), suggested that BKP may be superior in restoring vertebral height, but both procedures restored some vertebral height reduction, kyphosis, Cobb angle, and wedge angle, and showed benefit in pain reduction and patient-reported functional improvement. However, it is not possible to definitively conclude whether BKP or PVP is superior in reducing pain and restoring function because many studies that examined all 3 variables did not report statistically significant results, and more definitive studies and data analysis are needed to confirm this finding (Figs.…”
Section: Which Is Better With Pvp Versus Bkp?mentioning
confidence: 99%
“…[1]Osteoporosis has become more prevalent in the elderly population due to decreased bone density and bone quality, microstructural damage, and increased bone fragility, resulting in systemic bone diseases prone to fractures. [2][3][4] One common complication of osteoporosis in the elderly is osteoporotic vertebral compression fractures (OVCF). OVCF often occurs in the thoracolumbar region of elderly individuals with osteoporosis, causing signi cant pain and limited mobility, severely impacting the quality of life.…”
Section: Introductionmentioning
confidence: 99%